Lietuvių kalbos kintamųjų garsų [ie], [uo] eksperimentinė analizė - Bacevičiūtė, Rima (Kalbotyra, 2002)
This paper presents the results of an experimental research of [ie] and [uo] – in the analysis they were contrasted in length and quality with the corresponding nearest monophthongs. It has been established that the polyphthongs are 1,61 times longer than the monophthongs, and in this respect they are closer to the diphthongs. The quality of the polyphthongs varies greatly: the beginning of [ie] is closest to the long [i.], its middle to [ẹ], and the end to [ȧ]; in the case of [uo] the beginning is closer to [u.], the middle to the open [ɔ], and the end to [a]. There is no rigid boundary between the first and second constituents. The range of the quality alteration is wider in the position —C rather than in —Ĉ, and the influence of the acute intonation is greater than that of the circumflex. These conclusions are arguments in favour of the monophonemic phonologic nature of the sounds under consideration.